RISK ASSESSMENT METHODOLOGY FOR A FORTHCOMING FLIGHT OF HELICOPTERS TAKING INTO ACCOUNT UNFAVORABLE METEOROLOGICAL CONDITIONS - A. L. Rybalkina; E. I. Trusova; V. D. Sharov (Научный вестник МГТУ ГА)
The task to provide flight safety is solved both at the stage of design and manufacture of aircraft and during its operation. Flight safety is influenced by three groups of factors: a human factor, a technical factor and marginal ambient conditions. In spite of the fact that only about 3% of aviation accidents are caused by marginal ambient conditions, in many cases there was a combination of the human factor as the main one with the availability of the accompanying unfavorable external conditions, especially marginal weather conditions. The article provides a comparative analysis of a flight safety factor in commercial civil aviation in the Russian Federation and the United States and analyzes accident statistics caused by adverse meteorological conditions. Since the greatest number of accidents related to marginal weather conditions occurred with helicopters, the article has highlighted the possibility of increasing helicopter flight safety by creating a methodology for risk assessment associated with the influence of adverse weather conditions before the flight operation. Risk assessment techniques, such as the ICAO Risk Assessment Matrix, the CFIT checklist, FRAT, have been analyzed and the feasibility of using the FRAT methodology has been demonstrated. On the basis of the FRAT methodology after updating the section "Operating conditions of the aircraft", a risk assessment methodology for the forthcoming flight of helicopters was obtained. A risk level admissibility scale for the forthcoming flight was proposed to interpret the obtained values of the risk level.